Optimization Of Manet Routing Using Hybrid DSR with ABC Algorithm - Patnala, Eswar; Giduturi, Srinivasa Rao (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Different mobile nodes are linked together through wireless networks using a system that is independent, self-configuring, and infrastructure-free called a MANET. AODV, DSDV, TORA, DSR& other routing protocols are used in Mobile Ad Hoc Networks (MANET). Mobility, overhead, battery depletion, delay, and interference are just a few of the problems and limitations that MANETs face because of their constantly changing topologies and lack of infrastructure. The best and optimal solution can be discovered using a variety of optimization techniques. Meta heuristics called "nature inspired algorithms" imitate nature to solve optimization issues, ushering in a new era of computation. The Artificial Bee Colony (ABC) program, developed by Karaboga, reproduces foraging behaviorof honey bees. Since ABC’s beginnings, extensive study has been done to improve its effectiveness and expand its applications.